Effects of urbanization on orchid bee diversity and orchid pollination: From neotropical cloud forests to urban cores - Hernández-Rivera, Álvaro; Dáttilo, Wesley; Montoya, Bibiana; Villegas-Patraca, Rafael; González-Tokman, Daniel (The Science of the total environment, 2024)
Urbanization is a significant driver of land use change, profoundly impacting biodiversity and ecosystem services worldwide. However, its effects in the tropics, which host some of the planet's highest biodiversity, remain inadequately understood. Orchid bees (Apidae: Euglossini) are key pollinators in Neotropical ecosystems, playing crucial roles in maintaining floral diversity and reproductive success of orchids and other plant families. Yet, little is known about how urbanization influences their diversity and pollination. In this study, we analyzed the diversity and composition or orchid bee communities along an urbanization gradient which extends from the city center to the surrounding cloud forests, which bear high orchid endemism while being highly threatened. Along the same gradient, we further evaluated pollination of a model native orchid, Gongora galeata, which is exclusively pollinated by the bee Euglossa obrima. As expected, increasing urbanization led to a decrease in orchid bee diversity, as well as a clear separation in species composition between urban and non-urban sites and a reduction in G. galeata pollination (i.e. fruit production). However, contrary to our expectations, orchid pollination also decreased with environmental heterogeneity and the abundance of its specific pollinator. Despite urban areas still hosting orchid bee species, our results reveal clear negative effects of urbanization not only on diversity, but also on the ecosystem function of a highly threatened group of bees. This study highlights the importance of considering local factors of urban landscapes for preserving not only biodiversity, but also fundamental ecological processes in cities. [Display omitted] •Urbanization threats mutualistic relationships between orchids and pollinator bees.•Orchid bee communities are different and less diverse in urban than natural sites.•High pollinator abundance does not guarantee effective orchid pollination.•Urbanization drivers of species loss are different from drivers of function loss.